Adaptation of the positive risk-taking scale in adolescents to Turkish: A study of linguistic equivalence, validity, and reliability - ERDEN ÇINAR, SEVAL (My University, 2023)
Bu çalışmada, Duell (2018) tarafından geliştirilen Ergenlerde Pozitif Risk Alma Davranışı Ölçeği’nin Türkçe’ye uyarlanması amaçlanmıştır. Ölçeğin psikometrik özellikleri, katılımcılarının İstanbulda ikamet eden lise öğrencileri olduğu üç farklı aşama ile sınanmıştır. Araştırmanın, dilsel eş değerliği 30, geçerlik ve güvenirlik analizleri 359 lise öğrencisi ile gerçekleştirilmiştir. Ölçüm aracının özellikleri dilsel eşdeğerlik, geçerlik (yapı, ölçüt) ve Cronbach alfa güvenirlik katsayısı yöntemleriyle incelenmiştir. Ölçeğin ölçüt geçerlik sınamalarında Ergenlerde Pozitif Risk Alma Ölçeği, Ergenlerde Risk Alma Ölçeği, Olumlu Sosyal ve Saldırgan Davranış Ölçeği ve Ergen Prososyallik Ölçeği’nden yararlanılmıştır. Yapı geçerliği için gerçekleştirilen doğrulayıcı ve açımlayıcı faktör analizi sonuçları, Ergenlerde Pozitif Risk Alma Ölçeğinin tek faktörlü yapısının yeterli uyum değerlerine sahip olduğunu göstermiştir. Ayrıca Ergenlerde Pozitif Risk Alma Ölçeği, ergenlerde risk alma davranışı, olumlu sosyal ve saldırgan davranış ve ergen prososyalliği ile pozitif yönde anlamlı ilişkiler elde edilmiştir. Ölçeğin Cronbach alfa güvenirlik katsayısı .74 olarak hesaplanmıştır. Sonuç olarak araştırma bulguları ölçeğin, ergenlerin pozitif risk alma davranış düzeylerini değerlendirmede kullanılabilecek geçerli ve güvenilir bir ölçüm aracı olduğunu desteklemektedir.

This research was carried out to adapt the Positive Risk-Taking Behavior Scale for Adolescents developed by Duell (2018) into Turkish. The psychometric properties of the scale were tested in three different stages, the participants of which were high school students residing in Istanbul. The research was conducted with 30 high school students in the first stage aiming to test the linguistic equivalence of the measurement tool, 359 in the second stage aiming to test the validity and reliability of the scale. The features of the measurement tool were examined with linguistic equivalence, validity (construct, criterion) and Cronbach Alpha reliability test methods. Adolescent Positive Risk Taking Scale, Adolescent Risk Taking Scale, Positive Social and Aggressive Behavior Scale and Adolescent Prosociality Scale were applied to the participants for the validity tests of the scale. The results of confirmatory and exploratory factor analysis performed for construct validity showed that the single-factor structure of the Adolescent Positive Risk Taking Scale had sufficient concordance values. Also, as expected, the Adolescent Positive Risk-Taking Scale shows a significant positive correlation with risktaking behavior, prosocial and aggressive behavior, and adolescent prosociality in adolescents. The Cronbach Alpha reliability coefficient of the scale was calculated as 74. As a result, research findings support that the scale is a valid and reliable measurement tool that can be used to evaluate the positive risk-taking behavior levels of adolescents.
Keywords: risk alma; pozitif risk alma; ergenlik; davranış gelişimi; ölçek uyarlama; risk taking; positive risk taking; adolescence; behavioral development; scale adaptation